Mango value chain in Trinidad and Tobago,Guyana and St. Lucia: Measuring and reducing post-harvest losses - Mohammed, M; Mpagalile, J; Lopez , V; Craig, k (Journal of Postharvest Technology, 2018)
Measurements of post-harvest losses of fresh mango fruits and processed mango products were conducted after screening the value chains  harvest losses of fresh mango fruits and processed mango products were conducted after screening the value chains  harvest losses of fresh mango fruits and processed mango products were conducted after screening the value chains  in Trinidad and Tobago, Guyana and St. Lucia. Based on the critical loss points (CLPs) where losses had the highest magnitude, the highest  in Trinidad and Tobago, Guyana and St. Lucia. Based on the critical loss points (CLPs) where losses had the highest magni in Trinidad and Tobago, Guyana and St. Lucia. Based on the critical loss points (CLPs) where losses had the highest magni impact on food security, and the highest effect on the economic result of the food supply chain (FSC), appropriate solutions were  impact on food security, and the highest effect on the economic result of the food supply chain (FSC), appropriate solutions  impact on food security, and the highest effect on the economic result of the food supply chain (FSC), appropriate solutions  recommended to optimize the system to reduce losses. The CLPs for fresh table ripe mangoes were similar in Trinidad and Tobago and  recommended to optimize the system to reduce losses. The CLPs for fresh table ripe mangoes were similar in T recommended to optimize the system to reduce losses. The CLPs for fresh table ripe mangoes were similar in T Guyana, with at harvest as CLP#1 and retail markets as CLP#4. For St. Lucia the CLPs identified for fresh mango fruits wholesaled to the  Guyana, with at harvest as CLP#1 and retail markets as CLP#4. For St. Lucia the CLPs identified for fresh mango fruits wholes Guyana, with at harvest as CLP#1 and retail markets as CLP#4. For St. Lucia the CLPs identified for fresh mango fruits wholes
Keywords: Post-harvest losses; enzymatic browning; physiological disorders; ripening; maturation harvest losses; enzymatic browning physiological disorders; ripeningmaturation